Fentanyl-Propofol Versus Ketamine-Propofol Combination for Sedation and Recovery in ERCP: A Double-Blinded Randomized Clinical Trial - Hanya Javaid, Muhammad Imran Riasat, Syed Junaid Shah, Maria Hashmi, Sagar Khurana, Farjad Sultan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The main goal of this study was to investigate the groups receiving fentanyl-propofol (fentP) against ketamine-propofol (ketP) in ERCP in terms of sedation, rescue sedation requirement, and recovery scores. Additionally, evaluated were the procedure's hemodynamic changes, postoperative pain score, complications, and endoscopist satisfaction. Methodology: A double-blinded randomized clinical trial was undertaken at the Dr. Ruth K.M. Pfau Civil Hospital Karachi's endoscopic room (DUHS) for six months. By using OPEN EPI sample size calculator, sample size was calculated. A total of 124 patients for elective ERCP were randomized into two groups by SNOSE protocol. Groups A and B, fentanyl-propofol (fentP) and ketamine-propofol (ketP), respectively, each contain 62 patients. All patients were given a loading dose of propofol 0.5 mg/kg, followed by a 75 ug/kg/minute infusion. The group fentP received fentanyl 1ml/kg (1 ug/kg) and the group ketP received ketamine 1ml/kg (0.5mg/kg). Ramsay sedation scores, the necessity for rescue sedation, and the Aldrete score post-operatively were noted. Hemodynamics during surgery and complications were also noted. Results: Sedation began noticeably earlier than usual in the group B at 0, 2 and 4 minutes (p-value <0.05), whereas sedation scores were higher in the group A at 8,10, and 15 minutes (p-value <0.05). Early sedation in the group B led to less consumption of rescue sedation doses (p-value <0.01). However, recovery scores were comparable in each groups (p-value >0.05). Conclusion: We were able to conclude that during ERCP, ketP had a significantly faster sedative onset than fentP, with less complication and a quicker recovery. Keywords: Propofol, KetP, FentP, ketamine, fentanyl, Sedation, Analgesia, ERCP, Monitored Anesthesia care.